FINANCIAL ANALYSIS OF THE INVESTMENT ATTRACTIVENESS OF THE ENTERPRISE - RZAEVA, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to study the concept of investment attractiveness of the enterprise. Outline of existing methods and areas of research. Research of existing theoretical approaches to understanding the concept of "investment attractiveness". Determining areas for assessing investment attractiveness according to the needs of financial analysis. It is advisable to study the company’s position in the market and its business reputation. It is important to calculate the integrated coefficient of investment attractiveness. It is important to calculate the ratio of borrowed and own funds, asset turnover ratio, current liquidity ratio, return on equity. It is important to set the parameters corresponding to the level of the standard position of the enterprise in the market. Emphasis is placed on assessing the level of the company’s dependence on competitors. It is important to study the profitability of products, return on investment. It is important to consider the strengths and weaknesses of the enterprise. It is appropriate to calculate the sales revenue index, the net profit index, the cost index, the long-term liability index. It is proposed to study the dynamics of the characteristics of financial stability, profitability, liquidity of assets and their turnover. The purpose of the article is achieved. Theoretical approaches to the concept are investigated. The directions of assessment are considered. The development of existing directions is offered. The needs of financial analysis are outlined. The directions of financial analysis of investment attractiveness are determined. Some results were obtained. It is proposed to assess the investment attractiveness of the enterprise based on the results of financial analysis. The basis of financial analysis is financial reporting. Analysis of financial condition is the basis for financial analysis. It is expedient to carry out the financial analysis in the following section: the analysis of liquidity of the enterprise, its solvency, financial stability, business and market activity, etc.